If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(X + 1) + 2(X + 1) = 24whatisX Reorder the terms: 2(1 + X) + 2(X + 1) = 24whatisX (1 * 2 + X * 2) + 2(X + 1) = 24whatisX (2 + 2X) + 2(X + 1) = 24whatisX Reorder the terms: 2 + 2X + 2(1 + X) = 24whatisX 2 + 2X + (1 * 2 + X * 2) = 24whatisX 2 + 2X + (2 + 2X) = 24whatisX Reorder the terms: 2 + 2 + 2X + 2X = 24whatisX Combine like terms: 2 + 2 = 4 4 + 2X + 2X = 24whatisX Combine like terms: 2X + 2X = 4X 4 + 4X = 24whatisX Solving 4 + 4X = 24ahistwX Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-24ahistwX' to each side of the equation. 4 + 4X + -24ahistwX = 24ahistwX + -24ahistwX Combine like terms: 24ahistwX + -24ahistwX = 0 4 + 4X + -24ahistwX = 0 Add '-4' to each side of the equation. 4 + 4X + -4 + -24ahistwX = 0 + -4 Reorder the terms: 4 + -4 + 4X + -24ahistwX = 0 + -4 Combine like terms: 4 + -4 = 0 0 + 4X + -24ahistwX = 0 + -4 4X + -24ahistwX = 0 + -4 Combine like terms: 0 + -4 = -4 4X + -24ahistwX = -4 Reorder the terms: 4 + 4X + -24ahistwX = -4 + 4 Combine like terms: -4 + 4 = 0 4 + 4X + -24ahistwX = 0 Factor out the Greatest Common Factor (GCF), '4'. 4(1 + X + -6ahistwX) = 0 Ignore the factor 4.Subproblem 1
Set the factor '(1 + X + -6ahistwX)' equal to zero and attempt to solve: Simplifying 1 + X + -6ahistwX = 0 Solving 1 + X + -6ahistwX = 0 Move all terms containing X to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + X + -1 + -6ahistwX = 0 + -1 Reorder the terms: 1 + -1 + X + -6ahistwX = 0 + -1 Combine like terms: 1 + -1 = 0 0 + X + -6ahistwX = 0 + -1 X + -6ahistwX = 0 + -1 Combine like terms: 0 + -1 = -1 X + -6ahistwX = -1 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| -5(m+8)=-2(m+8) | | -4=x-3/2 | | 3-2y-1=4y-7 | | 4x-18=9x+6 | | -9(4-x)-(1+7x)=-25 | | X+3y+27=0 | | 3/4×4= | | 9+2x+14=x+17 | | 3+c=13 | | 4/5÷8/9= | | 3a-4=-9 | | 4/5x-4=12 | | x^2y-3xy^2= | | -8y+24=-5(y-6) | | 3(2-b)=36 | | 5-x/6=1 | | 12-2x/48=3x-6/72 | | 120=-20x | | 2t+6=6t-10 | | 7x+8-4x=10 | | x^3+3x^2-25x=75 | | .08-.12(x-4)=.03(x-5) | | x-5+x+x+2=45 | | 7(2+2n)-7=-91 | | 7-5y=102 | | 3(-3)-y=7 | | 3/(2x-9)=8-3x | | 8-(w+7)=.5 | | (4/5)*5 | | 8(y-1)=6(2y-6) | | -3(v-4)=12-3v | | 2v+17=23 |